2021
DOI: 10.1016/j.amp.2020.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress among health care professionals of the three COVID-19 most affected Regions in Cameroon: Prevalence and associated factors

Abstract: Objectives. – The present study aimed to assess the prevalence of symptoms of anxiety and depression among health professionals in the three most affected regions in Cameroon. Materials and methods . – The study was a descriptive cross-sectional type. Participants were health care professionals working in the three chosen regions of Cameroon. The non_probability convinient sample technique and that of the snowball were valued via a web questionnaire. The non-exhaustive sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 10 publications
0
22
1
3
Order By: Relevance
“…Our results show that women were less likely to be anxious than men, as well as ANCTs versus nurses. These results are contrary to those reported by other authors, who concluded that ANCTs were more anxious than nurses [40], as well as the female gender [41,42]. There are more women in these professions, and this may explain the results obtained.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results show that women were less likely to be anxious than men, as well as ANCTs versus nurses. These results are contrary to those reported by other authors, who concluded that ANCTs were more anxious than nurses [40], as well as the female gender [41,42]. There are more women in these professions, and this may explain the results obtained.…”
Section: Discussioncontrasting
confidence: 99%
“…Les sujets de moins de 35 ans sont ceux qui ont le taux d’ESPT le plus important (score cumulé des cas positifs à 60 %). Nguépy Keubou et al [30] , dans une étude portant sur la détresse psychologique chez les travailleurs de santé au Cameroun dans le contexte de la Covid-19, ont souligné le fait que les jeunes adultes étaient davantage sujets à la détresse, du fait de leur manque d’expérience professionnelle, et surtout du fait que jeunes mariés et jeunes parents pour la plupart, ils avaient peur de contaminer leurs familles. On doit toutefois pondérer cette analyse dans le contexte de cette étude.…”
Section: Discussionunclassified
“…Few studies have attempted to evaluate the mental health impact of COVID-19 in Africa. In Cameroon, the prevalence of symptoms of anxiety and depression among health personnel is 42.2% and 43.5% respectively (Keubo et al , 2020). While in South Africa, another study reported depressive impacts of greater perceived COVID-19 infections precipitated by major societal changes from the lockdown (Kim et al , 2020).…”
Section: Available Mental Health Survey During Covid-19mentioning
confidence: 99%